The analogies toy: poetic algorithm as a composition strategy - Lôbo, Armando (Revista Vórtex, 2020)
This article aims to propose a ludic general strategy for composing music inspired by poetic analogies. It tries to expand the perspectives of algorithmic composition by considering multi-layered extramusical ideas as valid, successive steps to reach specific creative goals in music. While metaphorically preserving an overall algorithmic intention, this conception proposes the use of interdisciplinary factors as an alternative to mathematical procedures in formal plans of composition.